Universal Pre-K and College Enrollment: Is There a Link? - William T. Gormley; Sara Amadon; Katherine Magnuson; Amy Claessens; Douglas Hummel-Price (SAGE Publishing, 2023)
In this study, we used data from a cohort of 4,033 Tulsa kindergarten students to investigate the relationship between pre-K enrollment and later college enrollment. Specifically, we tested whether participation in the Tulsa Public Schools universal pre-K program and the Tulsa Community Action Project (CAP) Head Start program predicted enrollment in 2- or 4-year colleges. We used propensity score weighting with multiply imputed data sets to estimate these associations. We found that college enrollment was 12 percentage points higher for Tulsa pre-K alumni compared with former students who did not attend Tulsa pre-K or Head Start. College enrollment was 7.5 percentage points higher for Head Start alumni compared to former students who did not attend Head Start or Tulsa pre-K, but this difference was only marginally significant. Tulsa pre-K attendance was associated with 2-year college enrollment among students from all racial and ethnic backgrounds, but only among Black and Hispanic students did it strongly predict 4-year college enrollment.